Atrial natriuretic peptide (ANP) enhaces antioxidant capacity in experimental acute pancreatitis - Courreges, Ana Paula (2019)
We previously reported ANP attenuates the severity of acute pancreatitis by reducing trypsinogen activation and the inflammatory response. Recent studies support that endoplasmic reticulum (ER) stress and oxidative stress (OS) precede these events. Indeed, we showed that ANP attenuates ER stress and stimulates ER-dependent apoptosis. ER stress is intimately related to OS in the pathophysiology of numerous diseases. Given that the exocrine pancreas is rather susceptible to OS due to the extremely weak expression of antioxidant enzymes, in the present we sought to establish whether ANP affected OS in experimental AP by studding the main antioxidant (enzymatic and non-enzymatic) defense. AP was induced in Sprague-Dawley strain rats (200-220 g) by four repetitive cerulein injections (40 µg/Kg). Thirty minutes before the first cerulein injection animals were infused with either saline (control) or ANP (1 µg/Kg/h) for 60 min. Following euthanasia (60 min after the last cerulein injection) pancreatic samples were harvested for further assays (CICUAL-FFYB #4107/18). ANOVA followed by a Student’s t test modified by Bonferroni was used for statistical analysis. Results are expressed as the means±S.E.M. and p values of 0.05 or less were considered statistically significant. AP induces OS as previously reported. ANP stimulated Nrf-2 nuclear translocation (assessed by immunohistochemistry) which is a transcription factor that induces the expression of antioxidant enzymes (p<0.001). ANP also enhanced the activity of superoxide dismutase (SOD) (p<0.05), catalase (p<0.01) and glutathione transferase. Furthermore it also restored reduced glutathione and total glutathione levels (assessed by HPLC- tandem mass spectrometry) to control values (p<0.05). Present findings show that ANP enhances the antioxidant defense capacity of the exocrine pancreas in AP, further supporting its beneficial role in the disease.